Microaerobic Pretreatment of Sewage Sludge: Effect of Air Flow Rate, Pretreatment Time and Temperature on the Aerobic Process and Methane Generation - Ojeda-Reyes, O; Huilinir-Curio, C; Castillo-Reyes, A; Montalvo-Martinez, S (Elsevier Ltd, 2016)
The effect of air flow rate (AFR), pretreatment time, and temperature on a microaerobic pretreatment were determined, including its effect on CH4 generation. For this, four AFR (0.1, 0.3, 0.5 and 1 vvm), three temperatures (20, 25 and 35 °C) and three aeration times (24, 48 and 60 h) were evaluated in 1-L and 5-L bioreactors. The effect on CH4 production was evaluated in 280-mL bioreactors, using previously aerated sewage sludge. It was found that the micro-aerobic pretreatment improves the hydrolytic process, with an increase of proteins, total sugars, soluble chemical oxygen demand (COD), and a greater removal of volatile suspended solids (VSS) compared to a system without aeration. It was determined that an AFR = 0.3 vvm, 48 h of aeration time, and a temperature of 35 °C were the best operational conditions for increasing hydrolysis rate. VSS removal under the aerobic pretreatment follows first order kinetics. Finally, the aeration pretreatment allows a 211% increase of methane generation compared to a process without pretreatment, improving also total COD and VSS removal. © 2016 Elsevier Ltd.